Advanced strategies for assessing the quality of agricultural products - Diana Creţu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The new developments in the agri-food product market in terms of quality, but also due to changes in the consumer behavior of agri-food products, it is necessary to implement new strategies on this market. These are primarily reflected in assessing and improving the quality of agri-food products. As will be presented in this paper, this evaluation process calls for the continued development of various economically efficient analysis methodologies. Their role is to provide safety, quality and traceability of products in the process of modeling, taking into account the needs of consumers and the legislative framework in place. The present paper will present the latest results with the help of modern science related to food and nutrition. Analytical techniques for assessing the quality of food products will also be presented according to their operating principles as well as other evaluation criteria. As well as methods used for this work, I mention the documentation and dissemination of specialized papers in Romania and abroad. As well as the results obtained, new approaches of the analysis strategies for the evaluation of the quality of the agrifood products will be presented.
Keywords: L15; Q18; O32; 330; modeling techniques; agri-food products; qualitative strategies